2021
DOI: 10.1038/s41398-020-01166-w
|View full text |Cite
|
Sign up to set email alerts
|

Lower functional hippocampal redundancy in mild cognitive impairment

Abstract: With an increasing prevalence of mild cognitive impairment (MCI) and Alzheimer’s disease (AD) in response to an aging population, it is critical to identify and understand neuroprotective mechanisms against cognitive decline. One potential mechanism is redundancy: the existence of duplicate elements within a system that provide alternative functionality in case of failure. As the hippocampus is one of the earliest sites affected by AD pathology, we hypothesized that functional hippocampal redundancy is protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 45 publications
(37 reference statements)
4
47
1
Order By: Relevance
“…These findings are consistent with earlier studies on AD pathology, where atrophy was reported in the hippocampus, amygdala, and entorhinal cortex. 26 , 53 , 54 These findings are also consistent with recent findings on the possible neuroprotective role of redundancy in the hippocampus 55 and other large-scale brain networks, 56 which may contribute to the observed differences between the subgroups. Our results also suggest that the occipital lobe played a more minor role in the performance of the model, consistent with Braak’s staging scheme, 57 where the occipital lobe is shown to be affected only at later stages of AD.…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with earlier studies on AD pathology, where atrophy was reported in the hippocampus, amygdala, and entorhinal cortex. 26 , 53 , 54 These findings are also consistent with recent findings on the possible neuroprotective role of redundancy in the hippocampus 55 and other large-scale brain networks, 56 which may contribute to the observed differences between the subgroups. Our results also suggest that the occipital lobe played a more minor role in the performance of the model, consistent with Braak’s staging scheme, 57 where the occipital lobe is shown to be affected only at later stages of AD.…”
Section: Discussionsupporting
confidence: 90%
“…As in previous reports with neurodegenerative diseases, 30 , 32 , 104–106 because our hypotheses hinged on differences between each neurodegenerative group and healthy controls, and given that demographic and behavioural features were not matched across neurodegenerative samples (bvFTD versus Parkinson’s disease versus Alzheimer’s disease), we focused on pairwise comparisons between demographically matched tandems: healthy controls versus bvFTD, healthy controls versus Parkinson’s disease, healthy controls versus Alzheimer’s disease ( Table 2 ). In addition, given that a significant difference was found in sex between bvFTD and healthy controls, we conducted additional group comparison analyses of covariance using permutation testing controlling for sex 107 ( Supplementary material ). Moreover, to rule out potential confounds of facial emotion recognition disturbances in bvFTD (particularly, for negative emotions), 108, 109 we also conducted additional group comparison analyses of covariance using permutation testing and controlling for feedback valence recognition ( Supplementary material ).…”
Section: Methodsmentioning
confidence: 99%
“…There has been growing use of ML to determine if brain network metrics can serve as classifiers of brain disorders with several high-profile reviews recently published ( Bassett et al, 2020 ; Braun et al, 2018 ; Parkes et al, 2020 ; Vu et al, 2018 ). Many of the canonical networks identified in rsfMRI studies (e.g., default mode network) have been of critical focus in studies of large-scale network plasticity in a range of brain disorders including schizophrenia ( de Filippis et al, 2019 ; Lefort-Besnard et al, 2018 ; Progar & May, 1988 ; Steardo et al, 2020 ), autism ( L. Chen et al, 2020 ; Glerean et al, 2016 ; Hegarty et al, 2017 ), Alzheimer’s disease and related dementias ( Langella et al, 2021 ; Pellegrini et al, 2018 ; Salvatore et al, 2015 ), and brain injury ( Bonnelle et al, 2012 ; Caeyenberghs et al, 2017 ; Gilbert et al, 2018 ; Roy et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%